Reduction of Cd(II), Ag(II) AND Cu(II) Using Rubber Seed Shell : Adsorption Isotherm and Kinetics - Hajar Athirah, Mohd Sukri (2013)
Increasing industry in Malaysia produce high amount of wastewater, thus increase the heavy metal contaminants that become global concern of environment. Adsorption of heavy metals by activated carbon will need higher cost compare to the other adsorbents. Thus, an alternative way of waste utilization is initializing by researcher to reduce wastewater management cost. The objective of this research is to investigate the potential of rubber seed shell as alternative adsorbent to reduce Cd(II), Ag(II) and Cu(II) ions from aqueous solution by find its kinetic and adsorption isotherm using batch techniques. The adsorbent and adsorbate prepared is used for testing the effect of removal of the ions by the variation parameters of solution pH (pH2, Ph4,pH6 pH8,pH10), contact time (40min, 60min, 80min, 100min, 120min), adsorbent dosage (0.1g, 0.2g, 0.3g, 0.4g, 0.5g) and initial concentration (20ppm, 40ppm, 60ppm, 80ppm, 100ppm). The optimum ph=6, effective time and dosage of 120min and 0.3g is use through all parameters variation. All the experiments are using batch adsorption process and finalize by shake using rotary shaker and analyze using Atomic Absorption Spectroscopy (AAS). This adsorption case fit Langmuir isotherm with correlation coefficient of 0.9991 and satisfactory Pseudo-second order kinetic with correlation coefficient of 1 for all metal and adsorption constant range 0.0662 to 0.1873 g/mg.min. This research approved that rubber seed shell can be used as an alternative adsorbent to reduce Cd (II), Ag (II) and Cu (II) ions from aqueous solution.